MAKNA SIMBOLIS ORNAMEN-ORNAMEN PADA KELENTENG BOEN BIO SURABAYA - Febrianti, Kezia; Churota’ayun, Elisa (Seminar Nasional Ilmu Terapan, 2024)
The aim of this study is to describe the types of ornaments found in the Boen Bio Temple building at Jalan Kapasari No. 131 and their symbolic meanings. This study is descriptive and qualitative. The variety of ornaments found at the main building of Boen Bio Temple in Kapasan area was the focus of this research. Literature review, observation, documentation and interviews were used to collect the research data. A triangulation of the sources was carried out to verify the veracity of the data obtained. After data collection, the data was presented, reduced and conclusions were drawn. From the research results, the ornaments found in the outer and inner buildings of the Boen Bio Temple are as follows: Killin ornaments, a pair of lions, phoenix birds, 2 dragon poles, bats, five doors, 11 dragon lamps,4 entrance pillars, Zhong xiao lian jie ornaments,6 windows in the main room,5 lamps on the roof of the entrance, 2 paintings on the entrance wall. The results of this study shows that the use of ornaments in certain areas of the temple building has symbolic meanings are rich in moral values, one of which is a symbol of protection that can be passed on by these symbols for those who believe in them.